Biochemical and genetic role of apelin in essential hypertension and acute coronary syndrome. (15th November 2016) - Gupta, Mohit D.; Girish, MP; Shah, Dhaval; Rain, Manjari; Mehta, Vimal; Tyagi, Sanjay; Trehan, Vijay; Pasha, Qadar
Abstract: Background: Apelin-APJ pathway has emerged as a potent regulator of blood pressure (BP) and blood flow in vasculature and heart. Variants in apelin gene may affect the vascular tone in peripheral circulation or heart, thereby predisposing to cardiovascular diseases. The aim of our study was to investigate the association of two apelin gene polymorphisms rs3761581 and rs2235312, and apelin levels in patients with essential hypertension (EH) and acute coronary syndrome (ACS). Methods: The study comprised of three groups namely, (1) 118 healthy control subjects, (2) 92 EH patients, and (3) 60 ACS patients. DNA was extracted from peripheral blood leukocytes and genotyping was performed by SNaPshot method. Plasma apelin 13 levels were estimated using ELISA. Results: EH and ACS patients had a significantly lower level of apelin 13, regardless of gender ( p  = 0.003, p  = 0.017, respectively). Interestingly, the female EH and ACS patients had lower levels of apelin 13 than their male counterparts. The G allele of rs3761581 was more apparent in patients especially in ACS than the controls. Conclusion: Reduced apelin levels may enhance vasoconstriction to influence high BP and heart's workload in EH and ACS. Genetic involvement of apelin needs to be established in well-defined larger sample size.